إشكالية الفقر في الجزائر في ظل الأهداف الإنمائية للألفية الثالثة - لخضر, مرغاد; فطيمة, حاجي (Recherches économiques et managériales, 2013)
تعتبر قضية الفقر من أكبر التحديات التي تواجه العالم اليوم، حيث انه من بين 6 مليار نسمة من إجمالي عدد سكان العالم يعيش 2.8 مليار نسمة منهم على أقل من 2 دولار يوميا و 1.2 مليار نسمة يعيشون على اقل من 1 دولار يوميا في اليوم، وفي سنة 2000 تضمن تقرير الأمم المتحدة تأكيدا على أولوية محاربة الفقر في السياسات التنموية، والجزائر لم تهتم كثيرا بمكافحة الفقر في بداية الإصلاحات الاقتصادية، لكن مع تصاعد حدة الفقر وظهور انعكاساتها السلبية على المجتمع، أصبح الاهتمام بمكافحة الفقر يتزايد باستمرار، وفي هذا المجال نتساءل على واقع الفقر في الجزائر في ظل الاهداف الانمائية للأمم المتحدة. الكلمات المفتاحية: الفقر البشري، خط الفقر، مؤشرات الفقر، الاهداف الانمائية. Abstract  Poverty remains one of the biggest challenges facing the world today, Among 6 billions of the total world population 2.8 billion people are living on less than 2$ a day, and 1.2 billion on less than $1 a day. Moreover poverty is not only related to the under-developed countries and transition economies, but it is a widespread phenomenon for all nations with variant degrees of divergence. The analysis of poverty requires the determination of measurement standards of the phenomenon at the inter-nationanl level (international poverty line) as well as the national level (national poverty line). This paper aims to clarify the poverty phenomenon by pointing out its causes, and the ways to eradicate it on the Algeria. Key words:   poverty – poverty line – purchasing power parity –eradication of poverty.